RLP: interactive radio in Papua New Guinea - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
by Douglas Bell/Micael Olsson Douglas Bell and Micael Olsson explain how interactive radio programmes are helping tribes to save the rainforest and support agriculture in Papua New Guinea.